TEORES DE CARBONO ORGÂNICO TOTAL EM FUNÇÃO DO USO DO SOLO NO BIOMA CERRADO - BELUQUE, Giovanna; AMORIM, Luana Larissa de Souza; MAEKAWA, Simone Cândido Ensinas; HEID, Diego Menani (ANAIS DO ENIC, 2025)
-